Cain Furens Imitations Of Virgil and Ovid in Canto Six of Lucy Hutchinson's Order And Disorder - Hillier, Russell M. (2023)
The article examines Lucy Hutchinson's treatment of Cain and Abel in Canto Six of her biblical epic Order and Disorder. Hutchinson mobilises the classical tradition to elucidate the psychodrama of the fratricide Cain. Her imitation of four similes from Virgil's Aeneid and Georgics, and the allegorical figure of Envy from Ovid's Metamorphoses, helps to convey the dramatic shifts in Cain's psychological and spiritual state. Moreover, Hutchinson’s evocation of the reprobate Cain's restlessness through intertextual engagement with Virgil supports the Calvinist doctrine of double predestination. In Order and Disorder, Virgil and Ovid's Roman poems are aids to embellishing and enhancing the narrative and theology of Hutchinson's biblical epic.
Keywords: Lucy Hutchinson; Order and Disorder; Calvinism; Virgil; Ovid; Aeneid; Georgics; Metamorphoses